Clinical advances on Cardiac Insuffiency - Angel Julio Romero Cabrera; Benigno Figueiras Ramos.; Gerardo Rivero González (Medisur)
Cardiac insuffiency is a complex clinical syndrome which constitutes a common final path to get in by the majority of the cardiac diseases. Studies based on the communitarian surveys shows that from 30 to 40 % of the patients decease within the first year of the diagnosis. The rest of the patients (from 60 to 70 %) die within the 5 years after being diagnosed. For this reason it has been called as the ¨cancer of cardiology¨. The objective of this article is to update the advances reached in the clinical and therapeutic aspects of this important syndrome.